Práticas parentais de atividade física: um estudo comparativo e resultados de uma intervenção com o Triplo P Lifestyle em Grupo para pais - Cátia Sofia Pereira da Costa (2021)
The levels of overweight (OW) and obesity (OB) in children are worrying given the significant increase in recent decades. As parents are the main drivers of children's lifestyle change, family members are required to promote healthy behavior, such as the practice of regular physical activity. The present study aims (1) to compare the physical activity parenting practices perceived by parents of children with OW and OB and parents of children without OW and OB and (2) to evaluate the effects of Group Lifestyle Triple P (GLTP), a parental intervention, in the perception of physical activity parenting practices and in the levels of moderate and vigorous physical activity and sedentary activity of children aged 5 to 10 years, with OW and OB, followed in the Consultation on Nutritional Changes of the Centro Materno-Infantil do Norte (CMIN). This dissertation is part of the LifeStyle project, which is being developed by the Faculty of Psychology and Educational Sciences of the University of Porto. A Randomized Clinical Trial is under way to assess the effectiveness of the GLTP. For the purposes of the first objective, participants were, in addition to 57 parents from the LifeStyle project, 57 parents from a study on the psychometric properties of the Physical Activity Parenting Practices Questionnaire (PAPPQ). Results revealed that parents of children without OW and OB were more involved and facilitated children's frequency in the activities. Parents of children with OW and OB referred higher use of screen time, thus promoting a sedentary lifestyle. Regarding the second objective, participants in the LifeStyle project (N = 57) were randomly assigned to an intervention and a control group. They completed the assessment protocol before and after the intervention (M1 and M2). A family characterization questionnaire, the PAPPQ and an accelerometer were used. The results did not reveal statistically significant differences between groups, between M1 and M2, in all variables. However, and despite a few limitations, there were promising trends on the usefulness of GLTP in promoting practices that encourage physical activity and in reducing practices that discourage it. GLTP seems to act as a protective factor in moderate and vigorous and sedentary activity levels. It is expected that future studies will contribute to reveal the efficacy of the program.